2022
DOI: 10.3390/agronomy12020532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods for Measuring Fusarium-Damaged Kernels of Wheat

Abstract: Fusarium head blight (FHB) is one of the most economically destructive diseases of wheat (Triticum aestivum L.), causing substantial yield and quality loss worldwide. Fusarium graminearum is the predominant causal pathogen of FHB in the U.S., and produces deoxynivalenol (DON), a mycotoxin that accumulates in the grain throughout infection. FHB results in kernel damage, a visual symptom that is quantified by a human observer enumerating or estimating the percentage of Fusarium-damaged kernels (FDK) in a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The reflectance data were exported from the software in the form of Excel sheets using the export option. Following the method of estimating the percentage of Fusarium-damaged kernels (FDKs) developed by Ackerman [ 38 ], we collected the kernel damage percentage. This method quantifies visual symptoms with the help of human observation.…”
Section: Methodsmentioning
confidence: 99%
“…The reflectance data were exported from the software in the form of Excel sheets using the export option. Following the method of estimating the percentage of Fusarium-damaged kernels (FDKs) developed by Ackerman [ 38 ], we collected the kernel damage percentage. This method quantifies visual symptoms with the help of human observation.…”
Section: Methodsmentioning
confidence: 99%
“…Type II is assessed by rating the visual symptoms on the spikes, which appear as bleached, yellowish or discolored, and stunted (Zakieh et al, 2021;Steed et al, 2022). FDK is quantified traditionally by estimating the amount of visibly damaged kernels, which appear smaller, shriveled, and in a range of colors from pale pink to brown (Delwiche et al, 2010), according to a predetermined scale for visual assessments or by employing manual tools (Ackerman et al, 2022). Comparisons between both types of resistance (resistance types II and III) have revealed that it would be more efficient and consistent to estimate FHB than the degree of colonization on the spike (Agostinelli, 2009;Balut et al, 2013;Khaeim et al, 2019;Ackerman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Type II is assessed by rating the visual symptoms on the spikes, which appear as bleached, yellowish or discolored, and stunted ( Zakieh et al., 2021 ; Steed et al., 2022 ). FDK is quantified traditionally by estimating the amount of visibly damaged kernels, which appear smaller, shriveled, and in a range of colors from pale pink to brown ( Delwiche et al., 2010 ), according to a predetermined scale for visual assessments or by employing manual tools ( Ackerman et al., 2022 ). Comparisons between both types of resistance (resistance types II and III) have revealed that it would be more efficient and consistent to estimate FHB than the degree of colonization on the spike ( Agostinelli, 2009 ; Balut et al., 2013 ; Khaeim et al., 2019 ; Ackerman et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…FDK is quantified traditionally by estimating the amount of visibly damaged kernels, which appear smaller, shriveled, and in a range of colors from pale pink to brown ( Delwiche et al., 2010 ), according to a predetermined scale for visual assessments or by employing manual tools ( Ackerman et al., 2022 ). Comparisons between both types of resistance (resistance types II and III) have revealed that it would be more efficient and consistent to estimate FHB than the degree of colonization on the spike ( Agostinelli, 2009 ; Balut et al., 2013 ; Khaeim et al., 2019 ; Ackerman et al., 2022 ). However, screening by either manual or visual assessments is a labor- and time-consuming process for rating genotypes, is biased due to the subjectivity of visual assessments, and has low reproducibility among experiments ( Barbedo et al., 2015 ; Khaeim et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%